High-performance corrugated carton with waterproof and antibacterial functions and preparation process of high-performance corrugated carton
By applying a composite antibacterial coating liquid on the corrugated cardboard, the barrier enhancement coating and composite antibacterial coating are formed, which solves the problem of degradation of mechanical properties and bacterial growth after water absorption and moisture, and achieves a high-performance waterproof and antibacterial effect.
Patent Information
- Application Number
- CN202411735503.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-11-29
AI Technical Summary
The mechanical properties of existing corrugated cardboard decrease after absorbing water and getting damp, and the humid environment is prone to breed bacteria and mold, which poses a risk of harming packaging items and human health.
The composite antibacterial coating liquid is used, including modified epoxy resin emulsion, antibacterial agent, curing agent and organic solvent. By applying barrier enhancement coating liquid and composite antibacterial coating liquid on the inner and outer surfaces of corrugated cardboard, the barrier enhancement coating and composite antibacterial coating are formed to improve the waterproof and antibacterial properties of corrugated cardboard.
It realizes the waterproof and antibacterial function of corrugated cardboard, which can adaptively adjust the antibacterial effect under different ambient temperatures and humidity, extend the antibacterial time, and improve the mechanical strength and service life of corrugated cardboard.
Smart Images

Figure CN119754096A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of corrugated paper, and in particular to a high-performance corrugated paper box with waterproof and antibacterial functions and a preparation process thereof. Background Art
[0002] Corrugated paperboard is the most widely used packaging product, which is made of corrugated paperboard through die-cutting, creasing, nailing or gluing. Corrugated paperboard is a multi-layer adhesive body, which is usually composed of at least one layer of corrugated core paper (commonly known as "corrugated paper core"), one layer of inner paperboard and one layer of outer paperboard, and has high mechanical strength. There are three main advantages of using corrugated paperboard as packaging material: 1) Low production cost, the packaging container made is light and foldable, easy to store and transport, and the cost of base paper is much lower than other materials such as plastic and metal; 2) It is easy to recycle and meet the requirements of green packaging. After recycling, corrugated paperboard can be used as raw material for pulp or molding production, and corrugated paperboard can also be produced again; 3) It is easy to process and shape, and can be processed into the packaging container required for the product through die-cutting, creasing and folding, and the operation is simple and easy. The production process of corrugated cardboard has shown a high degree of automation and assembly line operation. Its continuous production line is to continuously complete corrugated pressing, gluing, lamination, drying and shaping on the same machine, with fast production speed, low cost and guaranteed corrugated cardboard quality (CN110306380B A waterproof and flame retardant coating for corrugated cardboard and its preparation method).
[0003] Conventional corrugated cardboard is hygroscopic. On the one hand, its mechanical properties will be greatly reduced after absorbing water and getting damp. On the other hand, a humid environment is prone to breeding bacteria and mold, posing a risk of endangering the packaged items and even human health.
[0004] Applying a waterproof coating on the surface of corrugated paperboard is a common method to improve its waterproof performance, such as patents CN115897284B_A method for producing waterproof and wear-resistant corrugated paperboard, CN116397461B_A waterproof and flame-retardant composite corrugated paperboard and its composite process, CN117966517B_A waterproof and flame-retardant corrugated paper and its preparation method; but these patents do not improve the antibacterial performance of corrugated paperboard, and the waterproof coating is not "waterproof". When the environmental humidity is high or it is wet, it is still easy to breed bacteria. And within the normal range of environmental temperature and humidity, the higher the temperature and humidity, the more conducive it is to the growth and reproduction of most bacteria and fungi.
[0005] Patent CN107447592B discloses a hydrophobic antibacterial agent for corrugated paperboard and a hydrophobic antibacterial reinforced corrugated paperboard and a preparation method thereof, which uses fumed silica as a carrier, loads a silane coupling agent and nano silver ions, and has both hydrophobic and antibacterial effects, and has excellent hydrophobic and antibacterial properties. However, facing the characteristic that the higher the temperature and humidity within a certain range, the easier it is to breed bacteria, the patent does not provide a reliable solution.
[0006] Therefore, it is necessary to improve the existing technology to provide a more reliable solution. Summary of the invention
[0007] The technical problem to be solved by the present invention is to provide a high-performance corrugated paper box with waterproof and antibacterial functions and a preparation process thereof in view of the deficiencies in the above-mentioned prior art.
[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is: In a first aspect of the present invention, a preparation process of a high-performance corrugated paper box with waterproof and antibacterial functions is provided, comprising the following steps:
[0009] S1. Provide corrugated cardboard substrate;
[0010] S2, coating the barrier enhancement coating liquid on the inner and outer surfaces of the corrugated paperboard substrate respectively, and forming a barrier enhancement coating after curing;
[0011] S3, applying a composite antibacterial coating liquid on the surface of the barrier enhancement coating, and forming a composite antibacterial coating after curing to obtain a composite corrugated paperboard;
[0012] S4, using the composite corrugated paperboard to make the high-performance corrugated paperboard box with waterproof and antibacterial functions;
[0013] The composite antibacterial coating comprises the following raw material components in parts by weight: 80-120 parts of modified epoxy resin emulsion, 8-17 parts of antibacterial agent, 15-28 parts of curing agent, and 65-105 parts of organic solvent;
[0014] Wherein, the antibacterial agent is prepared by the following method:
[0015] S3-1, preparing amino-modified nanoporous silica;
[0016] S3-2, preparing titanium-doped carbon dots;
[0017] S3-3, using aminated nanoporous silica as a carrier and titanium-doped carbon dots as an active antibacterial component, loading titanium-doped carbon dots on aminated nanoporous silica to obtain carbon dot-silica composite particles;
[0018] S3-4, coating the surface of the carbon dot-silicon dioxide composite particles with an adaptive protective film to obtain the antibacterial agent.
[0019] Preferably, step S3-1 is specifically:
[0020] S3-1-1, add 3-12 mL of ethanol and 0.03-0.18 g of hexadecyltrimethylammonium bromide to 20-80 mL of deionized water, stir for 5-30 min, then drop 1-4 mL of triethanolamine, stir for 5-30 min, heat to 55-70 ° C, drop 1.5-6 mL of a mixture of ethyl orthosilicate and 0.15-0.6 mL of aminopropylmethyldiethoxysilane under stirring at 1000-4000 rpm, maintain the current temperature, and react for 2 hours under stirring at 500-1000 rpm;
[0021] S3-1-2. Transfer the product obtained in step S3-1-1 to a reactor, react at 110-130°C for 24-72h, cool to room temperature, centrifuge and filter, add 15-60mL of a mixed washing solution consisting of 5wt% hydrochloric acid and 100-400mL of ethanol to the solid product, ultrasonicate for 15-60min, filter, wash the solid product with ethanol, and dry at 50-80°C to constant weight to obtain amino-modified nanoporous silica.
[0022] Preferably, step S3-2 is specifically:
[0023] S3-2-1, take 0.6-2.4g chitosan, add it to 50-150mL 1-3wt% acetic acid aqueous solution, stir for 3-10min, and obtain mixed solution 1;
[0024] S3-2-2, add 0.29-1.186 g of tetracarboxyphenylporphyrin, 0.384-1.536 g of citric acid, and 0.234-0.936 g of titanium oxalate into 50-200 mL of deionized water, and stir for 5-20 min to obtain a mixed solution 2;
[0025] S3-2-3. Add mixed solution 1 to mixed solution 2, stir for 10-40 minutes to obtain a precursor solution, transfer the precursor solution to a polytetrafluoroethylene-lined reactor, react at 170-210°C for 6-24 hours, cool to room temperature after the reaction, filter the product with a 0.22μm filter membrane, and dialyze the filtrate in deionized water with a dialysis bag with a molecular retention capacity of 1000D for 48 hours. Take the dialysate in the dialysis bag, rotary evaporate and freeze-dry to obtain titanium-doped carbon dots.
[0026] Preferably, step S3-3 is specifically:
[0027] S3-3-1, add 0.5-2g of amino-modified nanoporous silica into 25-100mL of deionized water, and disperse by ultrasonic for 5-30min to obtain a silica dispersion;
[0028] S3-3-2, adding 0.225-0.9 g of titanium-doped carbon dots into 25-100 mL of deionized water, and ultrasonically dispersing for 5-30 min to obtain a carbon dot dispersion;
[0029] S3-3-3. Add the carbon dot dispersion to the silica dispersion under stirring, shake on a shaker at 50-70°C and 80-200 rpm for 12-48 hours, filter, and vacuum dry the solid product at 60-80°C for 6-24 hours to obtain carbon dot-silica composite particles.
[0030] Preferably, step S3-4 is specifically:
[0031] Take 0.15-0.6g corn starch and 0.35-1.4g β-cyclodextrin, add them to 50-200mL distilled water, ultrasonically disperse for 10-30min, heat in a boiling water bath with stirring for 30-90min, keep stirring, add 0.25-1g carbon dot-silica composite particles, cool to 60-70℃ and continue stirring for 0.5-2h, let stand at 2-10℃ for 12-48h, filter, wash the solid product with ethanol, and vacuum freeze-dry to obtain an antibacterial agent.
[0032] Preferably, the modified epoxy resin emulsion is prepared by the following method:
[0033] Take 2.5-10g of amino silicone oil and 0.35-1.5g of OP-10 and add them to 20mL of toluene, stir at 60-70°C and 1000-4000rpm for 30-90min, then add 3-12g of epoxy resin E44 and 0.05-0.2g of 2-butyltin 2-laurate, heat and reflux at 72-80°C for 3-8h to obtain a modified epoxy resin emulsion.
[0034] Preferably, the organic solvent is toluene, and the curing agent is isophorone diamine;
[0035] The composite antibacterial coating is prepared by the following method:
[0036] 1) Divide toluene into two parts, add the antibacterial agent into the first part of toluene, and ultrasonically disperse for 5-30 minutes to obtain an antibacterial agent dispersion;
[0037] 2) Add the modified epoxy resin emulsion to the second part of toluene, stir for 5-20 minutes, add the antibacterial agent dispersion under stirring, stir for 10-45 minutes, then add isophorone diamine, continue stirring for 3-10 minutes, and obtain a composite antibacterial coating.
[0038] Preferably, the barrier enhancement coating solution is prepared by the following method:
[0039] S2-1, take 2.5-10g of graphene oxide and add it to a mixed acid consisting of 25-100mL of 10% H2O2 and 50-300mL of 95wt% concentrated sulfuric acid, heat and reflux at 70-85°C for 4-12h, filter, wash the solid product with deionized water until neutral, and vacuum dry at 60-90°C to constant weight to obtain pretreated graphene oxide;
[0040] S2-2, take 0.15-0.6g of pretreated graphene oxide and add it to 225-900mL of dimethylacetamide, ultrasonically disperse it for 1-4h, then add 17.5-70g of ethylenediamine and 3-6g of dicyclohexylcarbocyanine, ultrasonically disperse it for 5-30min, and then seal and react at 125-140℃ for 24-72h. After the reaction, add 50-200mL of ethanol to the product, let it stand for 6-24h, discard the supernatant, filter the lower precipitate, wash the solid product with deionized water and ethanol in turn, and vacuum dry it at 90-100℃ for 6-24h to obtain modified graphene oxide;
[0041] S2-2, adding 0.5-2 g of modified graphene oxide into 25-100 mL of deionized water, and ultrasonically dispersing for 30-90 min to obtain a modified graphene oxide dispersion;
[0042] S2-2, add 2.5-10g polyvinyl alcohol, 0.4-1.6g sorbitol, and 0.25-1g Tween 80 into 50-150mL deionized water, stir at 70-85°C for 5-20min, then add modified graphene oxide dispersion under stirring, and ultrasonically disperse for 30-90min to obtain a barrier enhancement coating.
[0043] Preferably, the preparation process of the high-performance corrugated paper box with waterproof and antibacterial functions comprises the following steps:
[0044] S1. Provide corrugated cardboard substrate;
[0045] S2. Apply the barrier enhancement coating liquid on the inner surface and the outer surface of the corrugated paperboard substrate respectively, and dry at 50-80° C. for 15-60 minutes to form a barrier enhancement coating with a thickness of 0.1-0.5 mm;
[0046] S3, applying a composite antibacterial coating on the surface of the barrier enhancement coating, curing at 60-80° C. for 3-8 hours to form a composite antibacterial coating with a thickness of 0.25-1 mm, and obtaining a composite corrugated paperboard;
[0047] S4. The composite corrugated paperboard is die-cut, crimped, and nailed / glued to produce the high-performance corrugated paper box with waterproof and antibacterial functions.
[0048] A second aspect of the present invention provides a high-performance corrugated paper box with waterproof and antibacterial functions, which is prepared by the process as described above.
[0049] The beneficial effects of the present invention are:
[0050] The present invention provides a high-performance corrugated paperboard with waterproof and antibacterial functions. In the present invention, the corrugated paperboard can be endowed with excellent antibacterial properties by adding an antibacterial agent, and the antibacterial properties can be adaptively adjusted within a certain range according to the difference in ambient temperature and humidity. Specifically, when the ambient temperature and / or humidity increase, the antibacterial properties provided by the antibacterial agent will be adaptively enhanced, thereby being able to well cope with the characteristic that the higher the temperature and humidity within a certain range, the easier it is for bacteria to grow on the surface of the corrugated paperboard, and being able to provide a long-lasting antibacterial effect;
[0051] The present invention can improve the waterproof performance of the composite corrugated paperboard through the composite antibacterial coating, and give it excellent antibacterial performance by generating active oxygen substances and the like. By cooperating the barrier enhancement coating with the composite antibacterial coating and relying on the excellent barrier effect of the barrier enhancement coating, the risk of active oxygen brought by the composite antibacterial coating damaging the performance of the corrugated paperboard substrate can be avoided, while further improving the waterproof performance of the composite corrugated paperboard, and improving the mechanical strength of the composite corrugated paperboard, thereby ensuring its service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 The test results of active oxygen release of the antibacterial agent prepared in Example 1 at different relative humidity;
[0053] Figure 2 The test results of active oxygen release of the antibacterial agent prepared in Example 1 at different temperatures;
[0054] Figure 3 This is the infrared absorption spectrum of the titanium-doped carbon dots prepared in Example 1;
[0055] Figure 4 The results of antibacterial performance test. DETAILED DESCRIPTION
[0056] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.
[0057] It should be understood that the terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.
[0058] The test methods used in the following examples are conventional methods unless otherwise specified. The materials and reagents used in the following examples are all commercially available unless otherwise specified. In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.
[0059] The present invention provides a preparation process of a high-performance corrugated paper box with waterproof and antibacterial functions, comprising the following steps:
[0060] S1. Provide corrugated cardboard substrate;
[0061] S2. Apply the barrier enhancement coating liquid on the inner surface and the outer surface of the corrugated paperboard substrate respectively, and dry it at 50-80°C for 15-60 minutes to form a barrier enhancement coating with a thickness of 0.1-0.5 mm;
[0062] S3, applying a composite antibacterial coating on the surface of the barrier enhancement coating, curing at 60-80° C. for 3-8 hours to form a composite antibacterial coating with a thickness of 0.25-1 mm, and obtaining a composite corrugated paperboard;
[0063] S4. Composite corrugated cardboard is die-cut, embossed, and nailed / glued to produce high-performance corrugated boxes with waterproof and antibacterial functions.
[0064] In the present invention, the corrugated paperboard substrate may be a conventional commercial product or a homemade product based on a conventional method.
[0065] In the present invention, the barrier enhancement coating liquid is prepared by the following method:
[0066] S2-1, take 2.5-10g of graphene oxide and add it to a mixed acid consisting of 25-100mL of 10% H2O2 and 50-300mL of 95wt% concentrated sulfuric acid, heat and reflux at 70-85°C for 4-12h, filter, wash the solid product with deionized water until neutral, and vacuum dry at 60-90°C to constant weight to obtain pretreated graphene oxide;
[0067] S2-2, take 0.15-0.6g of pretreated graphene oxide and add it to 225-900mL dimethylacetamide (DMF), ultrasonically disperse for 1-4h, then add 17.5-70g of ethylenediamine (EDA) and 3-6g of dicyclohexylcarbocyanine (DCC), ultrasonically disperse for 5-30min, and then seal and react at 125-140°C for 24-72h. After the reaction, add 50-200mL of ethanol to the product, let it stand for 6-24h, discard the supernatant, filter the lower precipitate, wash the solid product with deionized water and ethanol in turn, and vacuum dry at 90-100°C for 6-24h to obtain modified graphene oxide;
[0068] S2-2, adding 0.5-2 g of modified graphene oxide into 25-100 mL of deionized water, and ultrasonically dispersing for 30-90 min to obtain a modified graphene oxide dispersion;
[0069] S2-2, add 2.5-10g polyvinyl alcohol, 0.4-1.6g sorbitol, and 0.25-1g Tween 80 into 50-150mL deionized water, stir at 70-85°C for 5-20min, then add modified graphene oxide dispersion under stirring, and ultrasonically disperse for 30-90min to obtain a barrier enhancement coating.
[0070] In the present invention, the composite antibacterial coating comprises the following raw material components in parts by weight: 80-120 parts of modified epoxy resin emulsion, 8-17 parts of antibacterial agent, 15-28 parts of curing agent and 65-105 parts of organic solvent.
[0071] In a preferred embodiment, the organic solvent is toluene and the curing agent is isophorone diamine.
[0072] In a preferred embodiment, the composite antibacterial coating is prepared by the following method:
[0073] 1) Divide toluene into two parts, add the antibacterial agent into the first part of toluene, and ultrasonically disperse for 5-30 minutes to obtain an antibacterial agent dispersion;
[0074] 2) Add the modified epoxy resin emulsion to the second part of toluene, stir for 5-20 minutes, add the antibacterial agent dispersion under stirring, stir for 10-45 minutes, then add isophorone diamine, continue stirring for 3-10 minutes, and obtain a composite antibacterial coating.
[0075] In the present invention, the modified epoxy resin emulsion is prepared by the following method:
[0076] Take 2.5-10g of amino silicone oil and 0.35-1.5g of OP-10 and add them to 20mL of toluene. Stir at 60-70°C and 1000-4000rpm for 30-90min. Then add 3-12g of epoxy resin E44 and 0.05-0.2g of 2-butyltin 2-laurate (DBTDL). Heat and reflux at 72-80°C for 3-8h to obtain a modified epoxy resin emulsion.
[0077] In the present invention, the antibacterial agent is prepared by the following method:
[0078] S3-1. Preparation of amino-modified nanoporous silica:
[0079] S3-1-1, add 3-12 mL of ethanol and 0.03-0.18 g of hexadecyltrimethylammonium bromide to 20-80 mL of deionized water, stir for 5-30 min, then drop 1-4 mL of triethanolamine, stir for 5-30 min, heat to 55-70 ° C, drop 1.5-6 mL of a mixture of ethyl orthosilicate and 0.15-0.6 mL of aminopropylmethyldiethoxysilane under stirring at 1000-4000 rpm, maintain the current temperature, and react for 2 hours under stirring at 500-1000 rpm;
[0080] S3-1-2. Transfer the product obtained in step S3-1-1 to a reactor, react at 110-130°C for 24-72h, cool to room temperature, centrifuge and filter, add 15-60mL of a mixed washing solution consisting of 5wt% hydrochloric acid and 100-400mL of ethanol to the solid product, ultrasonicate for 15-60min, filter, wash the solid product with ethanol, and dry at 50-80°C to constant weight to obtain amino-modified nanoporous silica.
[0081] S3-2, preparation of titanium-doped carbon dots:
[0082] S3-2-1, take 0.6-2.4g chitosan, add it to 50-150mL 1-3wt% acetic acid aqueous solution, stir for 3-10min, and obtain mixed solution 1;
[0083] S3-2-2, add 0.29-1.186 g of tetracarboxyphenylporphyrin, 0.384-1.536 g of citric acid, and 0.234-0.936 g of titanium oxalate into 50-200 mL of deionized water, and stir for 5-20 min to obtain a mixed solution 2;
[0084] S3-2-3. Add mixed solution 1 to mixed solution 2, stir for 10-40 minutes to obtain a precursor solution, transfer the precursor solution to a polytetrafluoroethylene-lined reactor, react at 170-210°C for 6-24 hours, cool to room temperature after the reaction, filter the product with a 0.22μm filter membrane, and dialyze the filtrate in deionized water with a dialysis bag with a molecular retention capacity of 1000D for 48 hours. Take the dialysate in the dialysis bag, rotary evaporate and freeze-dry to obtain titanium-doped carbon dots.
[0085] S3-3, using amino-modified nanoporous silica as a carrier and titanium-doped carbon dots as an active antibacterial component, titanium-doped carbon dots are loaded on the amino-modified nanoporous silica to obtain carbon dot-silica composite particles:
[0086] S3-3-1, add 0.5-2g of amino-modified nanoporous silica into 25-100mL of deionized water, and disperse by ultrasonic for 5-30min to obtain a silica dispersion;
[0087] S3-3-2, adding 0.225-0.9 g of titanium-doped carbon dots into 25-100 mL of deionized water, and ultrasonically dispersing for 5-30 min to obtain a carbon dot dispersion;
[0088] S3-3-3. Add the carbon dot dispersion to the silica dispersion under stirring, shake on a shaker at 50-70°C and 80-200 rpm for 12-48 hours, filter, and vacuum dry the solid product at 60-80°C for 6-24 hours to obtain carbon dot-silica composite particles.
[0089] S3-4. Coating an adaptive protective film on the surface of carbon dot-silicon dioxide composite particles:
[0090] Take 0.15-0.6g corn starch and 0.35-1.4g β-cyclodextrin, add them to 50-200mL distilled water, ultrasonically disperse for 10-30min, heat in a boiling water bath with stirring for 30-90min, keep stirring, add 0.25-1g carbon dot-silica composite particles, cool to 60-70℃ and continue stirring for 0.5-2h, let stand at 2-10℃ for 12-48h, filter, wash the solid product with ethanol, and vacuum freeze-dry to obtain an antibacterial agent.
[0091] In the present invention, the composite antibacterial coating can improve the waterproof performance of the composite corrugated paperboard, and can give it excellent antibacterial performance by generating active oxygen species, etc., and by combining the barrier enhancement coating with the composite antibacterial coating, with the help of the excellent barrier effect of the barrier enhancement coating, the risk of active oxygen brought by the composite antibacterial coating damaging the performance of the corrugated paperboard substrate can be avoided, while further improving the waterproof performance of the composite corrugated paperboard and improving the mechanical strength of the composite corrugated paperboard. The main functions of the composite antibacterial coating and the barrier enhancement coating are described below.
[0092] 1. The main functions of composite antibacterial coating:
[0093] Conventional corrugated cardboard is hygroscopic. After absorbing water and getting wet, the mechanical properties will be greatly reduced. On the other hand, the humid environment is also prone to breeding bacteria and mold, which may endanger the packaged items and even human health. The present invention can solve the above problems by adding an antibacterial agent to the composite antibacterial coating liquid, which can improve the waterproof performance and impart antibacterial properties.
[0094] 1. The composite antibacterial coating is prepared by using modified epoxy resin as a film-forming substance and an antibacterial agent as an active component, wherein the modified epoxy resin is obtained by modifying epoxy resin E44 with amino silicone oil. The modification of amino silicone oil can improve the hydrophobicity of epoxy resin E44, increase the contact angle between the prepared composite antibacterial coating and water, and enhance its waterproof ability.
[0095] 2. The antibacterial agent of the present invention is a core-shell structure system with corn starch and β-cyclodextrin as the shell and carbon dot-silica composite particles as the core, wherein the carbon dot-silica composite particles are composed of titanium-doped carbon dots as active antibacterial components and amino-modified nanoporous silica as a carrier.
[0096] 2-1. First, the present invention uses hexadecyltrimethylammonium bromide as a template and synthesizes amino-modified nanoporous silica by a hydrothermal method;
[0097] Then, a titanium-doped carbon dot with antibacterial activity was synthesized by hydrothermal method with chitosan, tetracarboxyphenylporphyrin, citric acid as main raw materials and titanium oxalate as doping component;
[0098] Afterwards, the titanium-doped carbon dots are loaded onto the amino-modified nanoporous silica by means of the rich pore structure of the amino-modified nanoporous silica, thereby obtaining carbon dot-silica composite particles. During the loading process, the amino functional groups on the surface of the nanoporous silica promote the connection of the titanium-doped carbon dots to the amino-modified nanoporous silica through electrostatic adsorption with functional groups such as carboxyl groups on the surface of the titanium-doped carbon dots.
[0099] Finally, corn starch and β-cyclodextrin were used as wall materials to coat the carbon dots-silica composite particles to obtain the final antibacterial agent.
[0100] 2-2, in the antibacterial agent, titanium-doped carbon dots show the ability to efficiently produce reactive oxygen species (ROS) under illumination. At the same time, the carbon dots also inherit the antibacterial properties of the precursor material chitosan. The titanium doped in the carbon dots can improve the efficiency of producing reactive oxygen under illumination by increasing the electron cloud density and active sites. The titanium-doped carbon dots in the present invention inherit the antibacterial mechanism of chitosan based on strong cationicity, and can adsorb and combine with the negative charge on the surface of microorganisms, resulting in damage to the bacterial cell wall, which is also consistent with the antibacterial mechanism of carbon dots in the dark state (Li P, Sun L, Xue S, et al. Recent advances of carbon dots as new antimicrobial agents [J]. Smart Materials (English), 2022 (002): 003.). At the same time, the carbon dots also have an antibacterial effect under illumination: under illumination, the carbon dots are stimulated to transition to an excited singlet state (S1), and the electrons in this state can pass through the intersystem crossing (ISC) to the excited triplet state (T1). Then, when the electrons return from the T1 state to the ground state (S0), phosphorescence (P) and reactive oxygen species (ROS) are generated. The generated ROS will cause non-specific damage to the bacterial cells, and ultimately play a bactericidal role. Therefore, the carbon dots of the present invention have antibacterial effects both under illumination and without illumination, and the antibacterial effect will be enhanced under illumination.
[0101] 2-3. In the antibacterial agent, the loading of amino-modified nanoporous silica endows the titanium-doped carbon dots with a sustained-release function of active components, which can prolong the antibacterial effect and effectively avoid the agglomeration of the titanium-doped carbon dots.
[0102] 2-4. In the antibacterial agent, after further coating with a wall material, it can obtain the function of adaptively adjusting the release rate of titanium-doped carbon dots, thereby adjusting the antibacterial effect of the antibacterial active component. Specifically, the adaptive protective film formed by corn starch and β-cyclodextrin has the characteristics of water solubility. When the humidity increases (such as the surface of the composite antibacterial coating is wet or damp, etc.), the release rate of titanium-doped carbon dots will increase, and when the ambient temperature rises, the release rate of titanium-doped carbon dots will also increase, thereby enhancing the antibacterial effect of the composite antibacterial coating. When the humidity and temperature in the environment increase, it is conducive to the growth of most bacteria and molds. Therefore, the adaptive increase in the antibacterial effect at this time can just cope with the accelerated growth of bacteria and molds, and achieve an adaptive adjustment effect.
[0103] 2-5. In the antibacterial agent, the amino-modified nanoporous silica, in addition to being a carrier, can also improve the surface roughness of the composite antibacterial coating and increase the contact angle between the surface and water, thereby improving the waterproof performance of the composite antibacterial coating, due to its nanoparticle structure.
[0104] 2. The main functions of barrier enhancement coating:
[0105] (1) In the present invention, ethylenediamine is used to modify the pretreated graphene oxide by amino modification using a condensation agent method, and then the pretreated graphene oxide is mixed with polyvinyl alcohol to prepare a barrier enhancement coating liquid. Sorbitol as a plasticizer can improve the mechanical properties of the coating. With the help of the excellent mechanical properties of graphene oxide, the addition of modified graphene oxide can also improve the mechanical properties of the coating, and finally improve the mechanical strength of the prepared composite corrugated paperboard.
[0106] (2) On the other hand, the addition of modified graphene oxide can form a layered stacking structure in the prepared coating. This structure prolongs the penetration path of small molecules and can enhance the barrier performance, so that the barrier-enhanced coating has a good barrier ability to water, oxygen, etc., thereby reducing the erosion and damage of water, oxygen and other substances to the internal corrugated cardboard substrate and improving the service life of the corrugated cardboard.
[0107] (3) In the present invention, the composite antibacterial coating provides an antibacterial effect by generating active oxygen, etc., but if the active oxygen enters the corrugated cardboard substrate, it will cause the cellulose of the corrugated cardboard to decompose through oxidation and damage the mechanical strength of the corrugated cardboard, causing a negative impact; by providing a barrier enhancement coating, the above-mentioned negative impact brought by the composite antibacterial coating can be overcome by forming a barrier effect, and active oxygen and other substances can be prevented from entering the corrugated cardboard substrate, and the waterproof performance of the corrugated cardboard can also be further improved; therefore, through the combination of the barrier enhancement coating and the composite antibacterial coating, the corrugated cardboard can be given excellent antibacterial and waterproof properties, while its mechanical strength can be improved and its service life can be guaranteed.
[0108] The above is the overall concept of the present invention, and detailed embodiments and comparative examples are provided below on the basis of the overall concept of the present invention to further illustrate the present invention.
[0109] The sources of the main raw materials in the following examples and comparative examples are described as follows:
[0110] Graphene oxide, single-layer diameter 100-500nm, Beijing Beike New Materials Technology Co., Ltd.;
[0111] Polyvinyl alcohol, PVA1799, Jiangsu Rayen Environmental Protection Technology Co., Ltd.;
[0112] Chitosan, degree of deacetylation 91.8% Shanghai Quanyan Biotechnology Co., Ltd.;
[0113] Tetracarboxyphenylporphyrin (TCPP), cas:14609-54-2 Xi'an Qiyue Biotechnology Co., Ltd.;
[0114] β-Cyclodextrin, Shanghai Cathay Chemical Co., Ltd.;
[0115] Epoxy resin E44, brand: Baling Petrochemical, Haihongzhuang Chemical Technology Co., Ltd.;
[0116] Amino silicone oil, Jiangsu Runfeng Synthetic Technology Co., Ltd.;
[0117] 2-Butyltin-2-laurate (dibutyltin dilaurate), Jiangsu Haolong Chemical Co., Ltd.;
[0118] OP-10, dodecylphenol polyoxyethylene ether, Errek (Shandong) Chemical Group Co., Ltd.
[0119] In the following embodiments and comparative examples, a self-made corrugated paperboard substrate is used, and the corrugated paperboard substrate includes a surface paper layer, a corrugated paper core layer, and a lining paper layer arranged in sequence from the outside to the inside; the surface paper layer, the corrugated paper core layer, and the lining paper layer are prepared from the same raw materials, and are all prepared from the following components in parts by weight:
[0120] 65 parts of lignin fiber;
[0121] 13 parts corn starch;
[0122] 12 parts oxidized starch
[0123] Corn stalk powder 28 parts;
[0124] 8.5 parts of polyvinyl alcohol;
[0125] Polyacrylamide 6 parts;
[0126] 4.5 parts of carboxymethyl cellulose
[0127] 220 parts of water.
[0128] The preparation method is as follows:
[0129] 1) adding lignin fiber, corn straw powder, oxidized starch and corn straw powder into water, stirring evenly and then crushing, passing through a 100-mesh sieve, then adding polyvinyl alcohol, polyacrylamide and carboxymethyl cellulose, beating at 200 rpm and 70° C. for 30 min, and then standing for 2 h to obtain pulp;
[0130] 2) Drying and shaping the pulp liquid to prepare a surface paper layer and a lining paper layer; Making the pulp liquid into corrugated base paper, and then corrugating and shaping it to obtain a corrugated paper core layer;
[0131] 3) The surface paper layer, the corrugated paper core layer and the inner paper layer were bonded in sequence with adhesive (white latex, Dongguan Sanju Adhesive Technology Co., Ltd., model 925A, viscosity 9500Mpa.s), compacted with a flattening roller (pressure of 0.3MPa), and dried at 70°C for 4h.
[0132] Example 1
[0133] A high-performance corrugated paper box with waterproof and antibacterial functions, the preparation process of which comprises the following steps:
[0134] S1. Provide corrugated cardboard substrate;
[0135] S2. Apply the barrier enhancement coating liquid on the inner surface and the outer surface of the corrugated paperboard substrate respectively, and dry it at 65° C. for 30 minutes to form a barrier enhancement coating with a thickness of 0.2 mm;
[0136] S3, coating the surface of the barrier enhancement coating with a composite antibacterial coating liquid, curing at 70° C. for 5 h, forming a composite antibacterial coating with a thickness of 0.5 mm, and obtaining a composite corrugated paperboard;
[0137] S4. Composite corrugated cardboard is die-cut, embossed and nailed to produce high-performance corrugated boxes with waterproof and antibacterial functions.
[0138] In this embodiment, the barrier enhancement coating liquid is prepared by the following method:
[0139] S2-1, take 5g of graphene oxide and add it to a mixed acid consisting of 50mL of 10% H2O2 and 150mL of 95% concentrated sulfuric acid, heat and reflux at 80°C for 6h, filter, wash the solid product with deionized water until neutral, and vacuum dry at 70°C to constant weight to obtain pretreated graphene oxide;
[0140] S2-2. Take 0.3 g of the treated graphene oxide and add it to 450 mL of dimethylacetamide (DMF), ultrasonically disperse it for 2 hours, then add 35 g of ethylenediamine and 6 g of dicyclohexylcarbocyanine, ultrasonically disperse it for 10 minutes, and then seal and react at 135°C for 48 hours. After the reaction, add 100 mL of ethanol to the product, let it stand for 12 hours, discard the supernatant, filter the lower precipitate, wash the solid product with deionized water and ethanol in turn, and vacuum dry it at 90°C for 12 hours to obtain modified graphene oxide.
[0141] S2-2, taking 1 g of modified graphene oxide and adding it into 50 mL of deionized water, and ultrasonically dispersing it for 45 min to obtain a modified graphene oxide dispersion;
[0142] S2-2, take 5g of polyvinyl alcohol, 0.8g of sorbitol, and 0.5g of Tween 80 and add them to 70mL of deionized water, stir at 80°C for 10min, then add the modified graphene oxide dispersion under stirring, and ultrasonically disperse for 60min to obtain a barrier enhancement coating.
[0143] In this embodiment, the composite antibacterial coating liquid includes the following raw material components by weight: 100 parts of modified epoxy resin emulsion, 12 parts of antibacterial agent, 23 parts of isophorone diamine, and 85 parts of toluene. The composite antibacterial coating liquid is prepared by the following method:
[0144] 1) Divide toluene into two parts, add the antibacterial agent into the first part of toluene, and disperse by ultrasonic for 15 minutes to obtain an antibacterial agent dispersion;
[0145] 2) Add the modified epoxy resin emulsion to the second part of toluene and stir for 10 minutes. Add the antibacterial agent dispersion under stirring. After stirring for 20 minutes, add isophorone diamine and continue stirring for 5 minutes to obtain an antibacterial coating.
[0146] Wherein, the antibacterial agent is prepared by the following method:
[0147] S3-1. Preparation of amino-modified nanoporous silica:
[0148] S3-1-1, add 6 mL of ethanol and 0.09 g of hexadecyltrimethylammonium bromide to 40 mL of deionized water, stir for 15 min, then drop 2 mL of triethanolamine, stir for 15 min, heat to 65 ° C, add 3 mL of ethyl orthosilicate and 0.3 mL of aminopropylmethyldiethoxysilane (APTS) under stirring at 2000 rpm, maintain the current temperature, and stir at 1000 rpm for 2 h;
[0149] S3-1-2. Transfer the product obtained in step S3-1-1 to a reactor, react at 120°C for 48 hours, cool to room temperature, centrifuge and filter, add the solid product to a mixed washing solution consisting of 30 mL of 5wt% hydrochloric acid and 200 mL of ethanol, ultrasonicate for 30 minutes, filter, wash the solid product with ethanol three times, and dry at 65°C to constant weight to obtain amino-modified nanoporous silica.
[0150] S3-2, preparation of titanium-doped carbon dots:
[0151] S3-2-1, take 1.2 g of chitosan, add it into 75 mL of 1.5% acetic acid aqueous solution, stir for 5 min, and obtain mixed solution 1;
[0152] S3-2-2, add 0.593 g of tetracarboxyphenylporphyrin, 0.768 g of citric acid, and 0.468 g of titanium oxalate into 100 mL of deionized water, and stir for 10 min to obtain a mixed solution 2;
[0153] S3-2-3. Add mixed solution 1 to mixed solution 2, stir for 20 min to obtain a precursor solution, transfer the precursor solution to a polytetrafluoroethylene-lined reactor, react at 190°C for 10 h, cool to room temperature after the reaction, filter the product with a 0.22 μm filter membrane, and dialyze the filtrate in deionized water with a dialysis bag with a molecular retention capacity of 1000D for 48 h. Remove the dialysate in the dialysis bag, rotary evaporate and freeze-dry to obtain titanium-doped carbon dots.
[0154] S3-3, using amino-modified nanoporous silica as a carrier and titanium-doped carbon dots as an active antibacterial component, titanium-doped carbon dots are loaded on the amino-modified nanoporous silica to obtain carbon dot-silica composite particles:
[0155] S3-3-1. Take 1 g of amino-modified nanoporous silica and add it into 50 mL of deionized water. Ultrasonic dispersion is performed for 15 min to obtain a silica dispersion.
[0156] S3-3-2, taking 0.45 g of titanium-doped carbon dots and adding them into 50 mL of deionized water, and ultrasonically dispersing them for 15 min to obtain a carbon dot dispersion;
[0157] S3-3-3. Add the carbon dot dispersion into the silica dispersion under stirring, shake on a shaker at 60°C and 100 rpm for 24 hours, filter, and vacuum dry the solid product at 70°C for 12 hours to obtain carbon dot-silica composite particles.
[0158] S3-4. Coating an adaptive protective film on the surface of carbon dot-silicon dioxide composite particles:
[0159] Take 0.3g corn starch and 0.7g β-cyclodextrin and add them to 100mL distilled water, ultrasonically disperse for 15min, heat in a boiling water bath with stirring for 60min, keep stirring, add 0.5g carbon dot-silica composite particles, cool to 65℃ and continue stirring for 1h, let stand at 5℃ for 24h, filter, wash the solid product with ethanol, and vacuum freeze-dry to obtain an antibacterial agent.
[0160] Wherein, the modified epoxy resin emulsion is prepared by the following method:
[0161] 5 g of amino silicone oil and 0.75 g of OP-10 were added to 20 mL of toluene, stirred at 65 °C and 2000 rpm for 45 min, then 6 g of epoxy resin E44 and 0.1 g of 2-butyltin 2-laurate were added, and the mixture was heated under reflux at 78 °C for 5 h to obtain a modified epoxy resin emulsion.
[0162] Example 2
[0163] A high-performance corrugated paper box with waterproof and antibacterial functions, the preparation process of which comprises the following steps:
[0164] S1. Provide corrugated cardboard substrate;
[0165] S2. Apply the barrier enhancement coating liquid on the inner surface and the outer surface of the corrugated paperboard substrate respectively, and dry it at 65° C. for 30 minutes to form a barrier enhancement coating with a thickness of 0.2 mm;
[0166] S3, coating the surface of the barrier enhancement coating with a composite antibacterial coating liquid, curing at 70° C. for 5 h, forming a composite antibacterial coating with a thickness of 0.5 mm, and obtaining a composite corrugated paperboard;
[0167] S4. Composite corrugated cardboard is die-cut, embossed and nailed to produce high-performance corrugated boxes with waterproof and antibacterial functions.
[0168] In this embodiment, the barrier enhancement coating liquid is prepared by the following method:
[0169] S2-1, take 5g of graphene oxide and add it to a mixed acid consisting of 50mL of 10% H2O2 and 150mL of 95% concentrated sulfuric acid, heat and reflux at 80°C for 6h, filter, wash the solid product with deionized water until neutral, and vacuum dry at 70°C to constant weight to obtain pretreated graphene oxide;
[0170] S2-2. Take 0.3 g of the treated graphene oxide and add it to 450 mL of dimethylacetamide (DMF), ultrasonically disperse it for 2 hours, then add 35 g of ethylenediamine and 6 g of dicyclohexylcarbocyanine, ultrasonically disperse it for 10 minutes, and then seal and react at 135°C for 48 hours. After the reaction, add 100 mL of ethanol to the product, let it stand for 12 hours, discard the supernatant, filter the lower precipitate, wash the solid product with deionized water and ethanol in turn, and vacuum dry it at 90°C for 12 hours to obtain modified graphene oxide.
[0171] S2-2, taking 0.85 g of modified graphene oxide and adding it into 50 mL of deionized water, and ultrasonically dispersing it for 45 min to obtain a modified graphene oxide dispersion;
[0172] S2-2, take 5g of polyvinyl alcohol, 0.8g of sorbitol, and 0.5g of Tween 80 and add them to 70mL of deionized water, stir at 80°C for 10min, then add the modified graphene oxide dispersion under stirring, and ultrasonically disperse for 60min to obtain a barrier enhancement coating.
[0173] In this embodiment, the composite antibacterial coating liquid includes the following raw material components by weight: 100 parts of modified epoxy resin emulsion, 12 parts of antibacterial agent, 25 parts of isophorone diamine, and 82 parts of toluene. The preparation method of the composite antibacterial coating liquid is the same as that of embodiment 1.
[0174] Example 3
[0175] A high-performance corrugated paper box with waterproof and antibacterial functions, the preparation process of which comprises the following steps:
[0176] S1. Provide corrugated cardboard substrate;
[0177] S2. Apply the barrier enhancement coating liquid on the inner surface and the outer surface of the corrugated paperboard substrate respectively, and dry it at 65° C. for 30 minutes to form a barrier enhancement coating with a thickness of 0.2 mm;
[0178] S3, coating the surface of the barrier enhancement coating with a composite antibacterial coating liquid, curing at 70° C. for 5 h, forming a composite antibacterial coating with a thickness of 0.5 mm, and obtaining a composite corrugated paperboard;
[0179] S4. Composite corrugated cardboard is die-cut, embossed and nailed to produce high-performance corrugated boxes with waterproof and antibacterial functions.
[0180] In this embodiment, the barrier enhancement coating liquid is prepared by the following method:
[0181] S2-1, take 5g of graphene oxide and add it to a mixed acid consisting of 50mL of 10% H2O2 and 150mL of 95% concentrated sulfuric acid, heat and reflux at 80°C for 6h, filter, wash the solid product with deionized water until neutral, and vacuum dry at 70°C to constant weight to obtain pretreated graphene oxide;
[0182] S2-2. Take 0.35g of the treated graphene oxide and add it to 450mL of dimethylacetamide (DMF), ultrasonically disperse it for 2h, then add 38g of ethylenediamine and 6.5g of dicyclohexylcarbocyanine, ultrasonically disperse it for 10min, and then seal and react at 135°C for 48h. After the reaction, add 100mL of ethanol to the product, let it stand for 12h, discard the supernatant, filter the lower precipitate, wash the solid product with deionized water and ethanol in turn, and vacuum dry it at 90°C for 12h to obtain modified graphene oxide.
[0183] S2-2, taking 1.2 g of modified graphene oxide and adding it to 50 mL of deionized water, and ultrasonically dispersing it for 45 min to obtain a modified graphene oxide dispersion;
[0184] S2-2, take 5g of polyvinyl alcohol, 0.8g of sorbitol, and 0.5g of Tween 80 and add them to 70mL of deionized water, stir at 80°C for 10min, then add the modified graphene oxide dispersion under stirring, and ultrasonically disperse for 60min to obtain a barrier enhancement coating.
[0185] In this embodiment, the composite antibacterial coating liquid includes the following raw material components by weight: 100 parts of modified epoxy resin emulsion, 12 parts of antibacterial agent, 20 parts of isophorone diamine, and 80 parts of toluene. The composite antibacterial coating liquid is prepared by the following method:
[0186] 1) Divide toluene into two parts, add the antibacterial agent into the first part of toluene, and disperse by ultrasonic for 15 minutes to obtain an antibacterial agent dispersion;
[0187] 2) Add the modified epoxy resin emulsion to the second part of toluene and stir for 10 minutes. Add the antibacterial agent dispersion under stirring. After stirring for 20 minutes, add isophorone diamine and continue stirring for 5 minutes to obtain an antibacterial coating.
[0188] Wherein, the antibacterial agent is prepared by the following method:
[0189] S3-1. Preparation of amino-modified nanoporous silica:
[0190] S3-1-1, add 6 mL of ethanol and 0.09 g of hexadecyltrimethylammonium bromide to 40 mL of deionized water, stir for 15 min, then drop 2 mL of triethanolamine, stir for 15 min, heat to 65 ° C, add 3 mL of ethyl orthosilicate and 0.3 mL of aminopropylmethyldiethoxysilane (APTS) under stirring at 2000 rpm, maintain the current temperature, and stir at 1000 rpm for 2 h;
[0191] S3-1-2. Transfer the product obtained in step S3-1-1 to a reactor, react at 120°C for 48 hours, cool to room temperature, centrifuge and filter, add the solid product to a mixed washing solution consisting of 30 mL of 5wt% hydrochloric acid and 200 mL of ethanol, ultrasonicate for 30 minutes, filter, wash the solid product with ethanol three times, and dry at 65°C to constant weight to obtain amino-modified nanoporous silica.
[0192] S3-2, preparation of titanium-doped carbon dots:
[0193] S3-2-1, take 1.2 g of chitosan, add it into 75 mL of 1.5% acetic acid aqueous solution, stir for 5 min, and obtain mixed solution 1;
[0194] S3-2-2, add 0.593 g of tetracarboxyphenylporphyrin, 0.768 g of citric acid, and 0.468 g of titanium oxalate into 100 mL of deionized water, and stir for 10 min to obtain a mixed solution 2;
[0195] S3-2-3. Add mixed solution 1 to mixed solution 2, stir for 20 min to obtain a precursor solution, transfer the precursor solution to a polytetrafluoroethylene-lined reactor, react at 190°C for 10 h, cool to room temperature after the reaction, filter the product with a 0.22 μm filter membrane, and dialyze the filtrate in deionized water with a dialysis bag with a molecular retention capacity of 1000D for 48 h. Remove the dialysate in the dialysis bag, rotary evaporate and freeze-dry to obtain titanium-doped carbon dots.
[0196] S3-3, using amino-modified nanoporous silica as a carrier and titanium-doped carbon dots as an active antibacterial component, titanium-doped carbon dots are loaded on the amino-modified nanoporous silica to obtain carbon dot-silica composite particles:
[0197] S3-3-1. Take 1 g of amino-modified nanoporous silica and add it into 50 mL of deionized water. Ultrasonic dispersion is performed for 15 min to obtain a silica dispersion.
[0198] S3-3-2, taking 0.50 g of titanium-doped carbon dots and adding them into 50 mL of deionized water, and ultrasonically dispersing them for 15 min to obtain a carbon dot dispersion;
[0199] S3-3-3. Add the carbon dot dispersion into the silica dispersion under stirring, shake on a shaker at 60°C and 100 rpm for 24 hours, filter, and vacuum dry the solid product at 70°C for 12 hours to obtain carbon dot-silica composite particles.
[0200] S3-4. Coating an adaptive protective film on the surface of carbon dot-silicon dioxide composite particles:
[0201] Take 0.3g corn starch and 0.7g β-cyclodextrin and add them to 100mL distilled water, ultrasonically disperse for 15min, heat in a boiling water bath with stirring for 60min, keep stirring, add 0.5g carbon dot-silica composite particles, cool to 65℃ and continue stirring for 1h, let stand at 5℃ for 24h, filter, wash the solid product with ethanol, and vacuum freeze-dry to obtain an antibacterial agent.
[0202] Wherein, the modified epoxy resin emulsion is prepared by the following method:
[0203] 5 g of amino silicone oil and 0.75 g of OP-10 were added to 20 mL of toluene, stirred at 65 °C and 2000 rpm for 45 min, then 6 g of epoxy resin E44 and 0.1 g of 2-butyltin 2-laurate were added, and the mixture was heated under reflux at 78 °C for 5 h to obtain a modified epoxy resin emulsion.
[0204] Comparative Example 1
[0205] This example is basically the same as Example 1, except that no antibacterial agent is added to the composite antibacterial coating in this example.
[0206] Comparative Example 2
[0207] This example is basically the same as Example 1, except that:
[0208] The antibacterial agent in this example is prepared by the following method:
[0209] S3-1, preparing amino-modified nanoporous silica, the specific method is the same as that in Example 1;
[0210] S3-2, preparation of carbon dots:
[0211] S3-2-1, take 1.2 g of chitosan, add it into 75 mL of 1.5% acetic acid aqueous solution, stir for 5 min, and obtain mixed solution 1;
[0212] S3-2-2, add 0.593 g of tetracarboxyphenylporphyrin and 0.768 g of citric acid into 100 mL of deionized water, stir for 10 min, and obtain a mixed solution 2;
[0213] S3-2-3. Add mixed solution 1 to mixed solution 2, stir for 20 min to obtain a precursor solution, transfer the precursor solution to a polytetrafluoroethylene-lined reactor, react at 190°C for 10 h, cool to room temperature after the reaction, filter the product with a 0.22 μm filter membrane, and dialyze the filtrate in deionized water with a dialysis bag with a molecular retention capacity of 1000D for 48 h. Remove the dialysate in the dialysis bag, rotary evaporate and freeze-dry to obtain carbon dots.
[0214] S3-3, using amino-modified nanoporous silica as a carrier and carbon dots as an active antibacterial component, loading carbon dots on the amino-modified nanoporous silica to obtain carbon dots-silicon dioxide composite particles:
[0215] S3-3-1. Take 1 g of amino-modified nanoporous silica and add it into 50 mL of deionized water. Ultrasonic dispersion is performed for 15 min to obtain a silica dispersion.
[0216] S3-3-2, add 0.45 g of carbon dots into 50 mL of deionized water, and disperse by ultrasonic for 15 min to obtain a carbon dot dispersion;
[0217] S3-3-3. Add the carbon dot dispersion into the silica dispersion under stirring, shake on a shaker at 60°C and 100 rpm for 24 hours, filter, and vacuum dry the solid product at 70°C for 12 hours to obtain carbon dot-silica composite particles.
[0218] S3-4, coating the surface of the carbon dot-silicon dioxide composite particles with an adaptive protective film, the specific method is the same as that in Example 1.
[0219] Comparative Example 3
[0220] This example is basically the same as Example 1, except that:
[0221] In this example, epoxy resin emulsion is used to replace the modified epoxy resin emulsion in Example 1. The epoxy resin emulsion is prepared by the following method:
[0222] 6 g of epoxy resin E44 was added into 20 mL of toluene, and stirred at 65° C. and 2000 rpm for 45 min to obtain an epoxy resin emulsion.
[0223] Comparative Example 4
[0224] This example is basically the same as Example 1, except that:
[0225] The barrier enhancement coating in this example was prepared by the following method:
[0226] 5 g of polyvinyl alcohol, 0.8 g of sorbitol, and 0.5 g of Tween 80 were added into 70 mL of deionized water, and stirred at 80° C. for 10 min to obtain a barrier enhancement coating solution.
[0227] Performance Testing
[0228] 1. Test of active oxygen release performance of antimicrobial agents:
[0229] Weigh 1 g of the antibacterial agent prepared in Example 1 and spread it evenly on a glass surface dish, place it in a glass desiccator, control the temperature and humidity in the desiccator, ventilate for 5 min every 5 h, irradiate with a fluorescent lamp for 1 h every 5 h, and take samples and measure every 12 h. The method is as follows: put the antibacterial agent into a filter bag, then immerse the filter bag in 500 mL of anhydrous ethanol, soak it under ultrasound for 5 min, take it out and spread it evenly on the glass surface dish again, and continue to place it in the glass desiccator; for the anhydrous ethanol after immersion (i.e., the fluorescence test solution), the fluorescence intensity at an excitation wavelength of 488 nm and an emission wavelength of 525 nm is determined by a reactive oxygen species detection kit (Reactive Oxygen Species Assay Kit, Nanjing Fengmiao Biotechnology Co., Ltd.), and after the test, the anhydrous ethanol is sealed and stored, and continuously used for subsequent immersion and fluorescence detection.
[0230] The fluorescence intensity of the fluorescent test solution at different times is detected to determine the cumulative release of active oxygen at different times. The higher the fluorescence intensity, the higher the active oxygen content.
[0231] The test results are as follows Figure 1 and Figure 2 As shown:
[0232] according to Figure 1 , which shows the test results of active oxygen release at different relative humidity at 25°C. It can be seen that the active oxygen release increases with the increase of humidity;
[0233] according to Figure 2 , which illustrates the test results of active oxygen release at different temperatures under a relative humidity of 70%. It can be seen that the active oxygen release increases with the increase of temperature.
[0234] comprehensive Figure 1 and Figure 2 The test results show that the antibacterial agent of the present invention can generate and release active oxygen under light, and its release amount increases adaptively with the increase of temperature and humidity, and has self-regulating characteristics.
[0235] 2. Reference Figure 3 , is the infrared absorption spectrum of the titanium-doped carbon dots prepared in Example 1, illustrating the successful synthesis of the titanium-doped carbon dots.
[0236] 3. Antibacterial performance test
[0237] Test method: Using the inhibition ring method, Escherichia coli was used as the test bacteria. The composite corrugated cardboard was cut into a circular paper sample with a diameter of 10 mm. Escherichia coli was inoculated into the nutrient agar medium. After evenly spreading, the circular paper sample was placed in the center of the medium and cultured at 37°C for 48 hours. The diameter of the inhibition ring was determined by the cross method.
[0238] (1) The method of Example 1 was adopted to adjust the amount of antibacterial agent added in the composite antibacterial coating, and the other conditions remained unchanged. Several composite corrugated paperboards were prepared and tested according to the above method, and an illumination group and a non-illumination group were set up. The illumination group was irradiated with a fluorescent lamp for 1 hour every 5 hours, and the non-illumination group was always kept away from light.
[0239] The test results are as follows Figure 4 As shown in Table 1 below:
[0240] Table 1
[0241]
[0242] It can be seen from the test results that the composite corrugated paperboard prepared in Example 1 has antibacterial properties under both light and dark conditions, and the antibacterial properties are stronger under light, mainly due to the active oxygen efficiently produced by the antibacterial agent under light. When the corrugated box is in use, the composite antibacterial coating on the outer surface can usually be exposed to sunlight in many scenarios, and it is also more likely to be stained with water or damp, with a greater risk of breeding bacteria. Since the probability of being exposed to sunlight is also greater, it will show stronger antibacterial properties, which can just adapt to its characteristics of greater risk of breeding bacteria; the composite antibacterial coating on the inner surface is usually unable to be exposed to sunlight, and the antibacterial property is mainly achieved through the antibacterial mechanism of the antibacterial agent in the dark state, and the antibacterial performance is relatively weak, which can also match its characteristics of less risk of being damp.
[0243] (2) The antibacterial properties of the composite corrugated paperboards prepared in Examples 2-3 and Comparative Examples 1-5 were tested according to the above method, all under the same conditions as the illumination group in (1).
[0244] 4. A contact angle tester (Dataphysics OCA25-HTV1800, Germany) was used to measure the water contact angle of the composite antibacterial coating on the composite corrugated paperboard prepared in the examples and comparative examples.
[0245] 5. Bursting strength: The composite corrugated paperboards prepared in the examples and comparative examples were tested in accordance with the standard "GB / T6544-2008".
[0246] 6. Edge compression strength: The composite corrugated paperboards prepared in the examples and comparative examples were tested in accordance with the standard "GB / T6544-2008".
[0247] The test results are shown in Table 2:
[0248] Table 2
[0249] Diameter of inhibition zone / mm Water contact angle (°) Bursting strength(kPa) Edge compression strength (kN / m) Example 1 35 107.2 1241 6.1 Example 2 35 107.8 1227 6.0 Example 3 33 106.5 1237 6.1 Comparative Example 1 0 85.1 1179 5.9 Comparative Example 2 30 106.8 1243 6.1 Comparative Example 3 34 100.5 1226 6.0 Comparative Example 4 35 107.4 1014 5.5
[0250] It can be seen from the test results that the composite corrugated paperboards prepared in Examples 1-3 have excellent antibacterial properties and good waterproof properties, and at the same time can ensure high mechanical strength; no antibacterial agent was added to the composite antibacterial coating in Comparative Example 1, resulting in a significant decrease in both the antibacterial and waterproof properties; the decrease in antibacterial performance in Comparative Example 2 was attributed to the fact that no titanium was doped in the carbon dots, which reduced the efficiency of active oxygen generation; no modified epoxy resin was used in Comparative Example 3, and the hydrophobic property decreased; no modified graphene oxide was added to the barrier enhancement coating in Comparative Example 4, resulting in a decrease in mechanical strength.
[0251] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.
Claims
1. A process for preparing a high-performance corrugated paper box with waterproof and antibacterial functions, characterized in that: The following steps are involved: S1. Provide corrugated cardboard substrate; S2, coating the barrier enhancement coating liquid on the inner and outer surfaces of the corrugated paperboard substrate respectively, and forming a barrier enhancement coating after curing; S3, applying a composite antibacterial coating liquid on the surface of the barrier enhancement coating, and forming a composite antibacterial coating after curing to obtain a composite corrugated paperboard; S4, using the composite corrugated paperboard to make the high-performance corrugated paperboard box with waterproof and antibacterial functions; The composite antibacterial coating comprises the following raw material components in parts by weight: 80-120 parts of modified epoxy resin emulsion, 8-17 parts of antibacterial agent, 15-28 parts of curing agent, and 65-105 parts of organic solvent; Wherein, the antibacterial agent is prepared by the following method: S3-1, preparing amino-modified nanoporous silica; S3-2, preparing titanium-doped carbon dots; S3-3, using aminated nanoporous silica as a carrier and titanium-doped carbon dots as an active antibacterial component, loading titanium-doped carbon dots on aminated nanoporous silica to obtain carbon dot-silica composite particles; S3-4, coating the surface of the carbon dot-silicon dioxide composite particles with an adaptive protective film to obtain the antibacterial agent.
2. The process for preparing a high-performance corrugated paper box with waterproof and antibacterial functions according to claim 1, characterized in that: Step S3-1 is specifically as follows: S3-1-1, add 3-12 mL of ethanol and 0.03-0.18 g of hexadecyltrimethylammonium bromide to 20-80 mL of deionized water, stir for 5-30 min, then drop 1-4 mL of triethanolamine, stir for 5-30 min, heat to 55-70 ° C, drop 1.5-6 mL of a mixture of ethyl orthosilicate and 0.15-0.6 mL of aminopropylmethyldiethoxysilane under stirring at 1000-4000 rpm, maintain the current temperature, and react for 2 hours under stirring at 500-1000 rpm; S3-1-2. Transfer the product obtained in step S3-1-1 to a reactor, react at 110-130°C for 24-72h, cool to room temperature, centrifuge and filter, add 15-60mL of a mixed washing solution consisting of 5wt% hydrochloric acid and 100-400mL of ethanol to the solid product, ultrasonicate for 15-60min, filter, wash the solid product with ethanol, and dry at 50-80°C to constant weight to obtain amino-modified nanoporous silica.
3. The process for preparing a high-performance corrugated paper box with waterproof and antibacterial functions according to claim 2, characterized in that: Step S3-2 is specifically as follows: S3-2-1, take 0.6-2.4g chitosan, add it to 50-150mL 1-3wt% acetic acid aqueous solution, stir for 3-10min, and obtain mixed solution 1; S3-2-2, add 0.29-1.186 g of tetracarboxyphenylporphyrin, 0.384-1.536 g of citric acid, and 0.234-0.936 g of titanium oxalate into 50-200 mL of deionized water, and stir for 5-20 min to obtain a mixed solution 2; S3-2-3. Add mixed solution 1 to mixed solution 2, stir for 10-40 minutes to obtain a precursor solution, transfer the precursor solution to a polytetrafluoroethylene-lined reactor, react at 170-210°C for 6-24 hours, cool to room temperature after the reaction, filter the product with a 0.22μm filter membrane, and dialyze the filtrate in deionized water with a dialysis bag with a molecular retention capacity of 1000D for 48 hours. Take the dialysate in the dialysis bag, rotary evaporate and freeze-dry to obtain titanium-doped carbon dots.
4. The process for preparing a high-performance corrugated paper box with waterproof and antibacterial functions according to claim 3, characterized in that: Step S3-3 is specifically as follows: S3-3-1, add 0.5-2g of amino-modified nanoporous silica into 25-100mL of deionized water, and disperse by ultrasonic for 5-30min to obtain a silica dispersion; S3-3-2, adding 0.225-0.9 g of titanium-doped carbon dots into 25-100 mL of deionized water, and ultrasonically dispersing for 5-30 min to obtain a carbon dot dispersion; S3-3-3. Add the carbon dot dispersion to the silica dispersion under stirring, shake on a shaker at 50-70°C and 80-200 rpm for 12-48 hours, filter, and vacuum dry the solid product at 60-80°C for 6-24 hours to obtain carbon dot-silica composite particles.
5. The process for preparing a high-performance corrugated paper box with waterproof and antibacterial functions according to claim 4, characterized in that: Step S3-4 is specifically as follows: Take 0.15-0.6g corn starch and 0.35-1.4g β-cyclodextrin, add them to 50-200mL distilled water, ultrasonically disperse for 10-30min, heat in a boiling water bath with stirring for 30-90min, keep stirring, add 0.25-1g carbon dot-silica composite particles, cool to 60-70℃ and continue stirring for 0.5-2h, let stand at 2-10℃ for 12-48h, filter, wash the solid product with ethanol, and vacuum freeze-dry to obtain an antibacterial agent.
6. The process for preparing a high-performance corrugated paper box with waterproof and antibacterial functions according to claim 1, characterized in that: The modified epoxy resin emulsion is prepared by the following method: Take 2.5-10g of amino silicone oil and 0.35-1.5g of OP-10 and add them to 20mL of toluene, stir at 60-70°C and 1000-4000rpm for 30-90min, then add 3-12g of epoxy resin E44 and 0.05-0.2g of 2-butyltin 2-laurate, heat and reflux at 72-80°C for 3-8h to obtain a modified epoxy resin emulsion.
7. The process for preparing a high-performance corrugated paper box with waterproof and antibacterial functions according to claim 1, characterized in that: The organic solvent is toluene, and the curing agent is isophorone diamine; The composite antibacterial coating is prepared by the following method: 1) Divide toluene into two parts, add the antibacterial agent into the first part of toluene, and disperse by ultrasonic for 5-30 minutes to obtain an antibacterial agent dispersion; 2) Add the modified epoxy resin emulsion to the second part of toluene, stir for 5-20 minutes, add the antibacterial agent dispersion under stirring, stir for 10-45 minutes, then add isophorone diamine, continue stirring for 3-10 minutes, and obtain a composite antibacterial coating.
8. The process for preparing a high-performance corrugated paper box with waterproof and antibacterial functions according to claim 1, characterized in that: The barrier enhancement coating solution is prepared by the following method: S2-1, take 2.5-10g of graphene oxide and add it to a mixed acid consisting of 25-100mL of 10% H2O2 and 50-300mL of 95wt% concentrated sulfuric acid, heat and reflux at 70-85°C for 4-12h, filter, wash the solid product with deionized water until neutral, and vacuum dry at 60-90°C to constant weight to obtain pretreated graphene oxide; S2-2, take 0.15-0.6g of pretreated graphene oxide and add it to 225-900mL of dimethylacetamide, ultrasonically disperse it for 1-4h, then add 17.5-70g of ethylenediamine and 3-6g of dicyclohexylcarbocyanine, ultrasonically disperse it for 5-30min, and then seal and react at 125-140℃ for 24-72h. After the reaction, add 50-200mL of ethanol to the product, let it stand for 6-24h, discard the supernatant, filter the lower precipitate, wash the solid product with deionized water and ethanol in turn, and vacuum dry it at 90-100℃ for 6-24h to obtain modified graphene oxide; S2-2, adding 0.5-2 g of modified graphene oxide into 25-100 mL of deionized water, and ultrasonically dispersing for 30-90 min to obtain a modified graphene oxide dispersion; S2-2, add 2.5-10g polyvinyl alcohol, 0.4-1.6g sorbitol, and 0.25-1g Tween 80 into 50-150mL deionized water, stir at 70-85°C for 5-20min, then add modified graphene oxide dispersion under stirring, and ultrasonically disperse for 30-90min to obtain a barrier enhancement coating.
9. The process for preparing a high-performance corrugated paper box with waterproof and antibacterial functions according to claim 1, characterized in that: The following steps are involved: S1. Provide corrugated cardboard substrate; S2. Apply the barrier enhancement coating liquid on the inner surface and the outer surface of the corrugated paperboard substrate respectively, and dry at 50-80° C. for 15-60 minutes to form a barrier enhancement coating with a thickness of 0.1-0.5 mm; S3, applying a composite antibacterial coating on the surface of the barrier enhancement coating, curing at 60-80° C. for 3-8 hours to form a composite antibacterial coating with a thickness of 0.25-1 mm, and obtaining a composite corrugated paperboard; S4, using the composite corrugated paperboard to undergo die-cutting, creasing, and nailing / gluing to produce the high-performance corrugated paper box with waterproof and antibacterial functions.
10. A high-performance corrugated paper box with waterproof and antibacterial functions, characterized in that: The method is prepared by the process as described in any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of carbon dot / chitosan in-situ composite material
CN104356430A
Nitrogen-doped porous hollow carbon sphere carbon dioxide adsorption material as well as preparation method and application thereof
CN106861618A
Hydrophobic antibacterial agent used for corrugated board, hydrophobic antibacterial reinforced corrugated board and preparation method thereof
CN107447592A
Near-infrared carbon quantum dot / silicon dioxide composite material as well as preparation method and application thereof
CN113234436A
Organic wastewater treatment agent and wastewater treatment method
CN116621314A
Cited By
Preparation method of antibacterial multifunctional optical film
CN122011471A
Multi-stage biological filter tower and photocatalytic malodorous gas purification device
CN122076206A
High-barrier packaging carton coating process and device based on biological mildew-proof coating
CN122880031A